Rancang Bangun Filter Air Berbasis Arduino Pada Penampungan Air Menggunakan Metode Fuzzy - Ponco Wiguna; Mochammad Hannats Hanafi Ichsan; Huriyatul Fitriyah (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Water is a source of life indispensable to living things, such as for daily necessities, transportation and as a source of energy such as for hydropower. Clean water is one type of water resource that has good quality and can be utilized by humans to be consumed or perform daily activities such as sanitation. Based on the problem given above, this research will make a tool that serves to clear and remove the acid content contained in water. This tool will work if the sensors in the water reservoir detect turbidity and acid levels. Data from the sensor will be processed by the microcontroller and will turn on the pump automatically if the turbidity is detected and the acid content is not appropriate. The value of the data on the sensor will be processed using the fuzzy method to get the output data in accordance with the results of data mapping to be executed by the actuator, this actuator is a pump that will deliver water to the filter. In the accuracy test of the sensor to determine the condition of this water is 94.21%. Based on examination of water purification system with turbid condition take time for approximately 7 hours, and at acid water condition this clarification process takes about 10 minutes by using alum as neutralizer for acid water condition. In the accuracy test of PWM on MATLAB aims to see the accuracy of the PWM value that can be seen on 20X4 LCD and compared with the value in MATLAB within the range of 0-255.